Highly selective, compact ultra-wide band bandpass filter using a novel multiple resonances resonator (MRR) - Khalid, S. (2013)
In this paper a high selective compact ultrawide band (UWB) bandpass filter has been designed using a novel multiple resonances resonator (MRR). Equivalent circuit has been extracted for the proposed single order MRR where the filtering function was derived, showing the feasibility of a maximum of six transmission poles in the passband. Finite frequency transmission zero was introduced by having a mixed coupling in the MRR structure, resulting in a compact UWB filter with high selectivity filtering response. A prototype is fabricated to validate the proposed design. Experimental and simulated results shows good agreement. Â© 2013 IEEE.